La construcción simbólica de la opinión pública - Garcés Corra, Raúl (Estudios sobre el Mensaje Periodístico, 2007)
This article deals with media roles in articulating consensus and reproducing establishment ideologies. It is analyzed public opinion as one of the most useful categories, invoked by journalists and politicians today, to illustrate consensus and to preserve the existing dominance relations. The last part of the article propose to examine specific media operations to construct reality, applying a methodology of discourse analysis to The New York Times´s coverage of Iraq´s war, three weeks before and one week after its outbreak.